Sodium nitrite detection in costal cartilage and vitreous humor – Case report of fatal poisoning with sodium nitrite. (July 2021) - Tomsia, Marcin; Głaz, Małgorzata; Nowicka, Joanna; Szczepański, Michał
Abstract: Medico-legal case reports very rarely describe sodium nitrite poisonings, but when they do most often they describe fatal suicide attempts. The case report presents a suicidal attempt with sodium nitrite of unknown provenance and the first attempt to detect nitrite ions in costal cartilage and vitreous humor samples. In February 2020, the corpse of a 23-year-old man was revealed in a student apartment. According to the prosecutor's office, the deceased had an incomplete IT (Information Technology) degree. The onsite inspection revealed the body on the bathroom floor, an opened container with sodium nitrite III in the bathroom cabinet, and a farewell letter in the apartment. The autopsy showed the hypoxia symptoms. The blood and urine of the deceased showed no trace of ethyl alcohol or psychoactive substances. Analyses showed the presence of nitrite ions in the blood (0.2 μg/ml) and urine (24.6 μg/ml) of the deceased. Additional analyses revealed nitrites presence in the gastric contents (2200 μg/ml), liver tissue (0.3 μg/g), kidney tissue (3.6 μg/g) and, for the first time, in costal cartilage (3.4 μg/g) and vitreous humor (57.7 μg/ml). The autopsy concluded that the cause of death was an acute cardio-respiratory failure in the course of suicidal sodium nitrite poisoning. The presented case indicates the need for collecting a wide range of samples for toxicological analyses. It also proves that both costal cartilage and vitreous humor may serve as an alternative forensic material in sodium nitrite poisonings. Highlights: Costal cartilage and vitreous humor can be used for nitrite presence analysis with the Griess method. Nitrites concentration in the gastric content suggested that the taken dose of sodium nitrite was only partially absorbed. Nitrites' concentration suggested that the ingested sodium nitrite was distributed in the organism and excreted via urinary system. Nitrites concentrations in the costal cartilage and vitreous humor reflected sodium nitrite accumulation in these tissues. As suggested by literature data, IT (Information Technology) background enabled the victim to gather information on suicide methods.